A Study on the Relationship between Gross Non-Performing Assets and Profitability of Selected Public and Private Sector Banks in India - Megha G; Bharath V (International Journal For Multidisciplinary Research, 2026)
In commercial banks, asset quality is one of the most important factors to assess the financial performance and stability of commercial banks. The negative impact on profitability of Non-Performing Assets (NPAs) includes a decline in interest income, an increase in provisioning and loss of financial strength of banks. The present study has examined the relationship Gross Non-Performing Assets (Gross NPA %) and Return on Assets (ROA) of selected Public Sector and Private Sector Banks in India for the period 2019-20 to 2023-24. The researcher has used secondary data from the published annual reports and audited financial statements of 10 major/commercial banks out of which 5 are Public Sector Banks (State Bank of India, Canara Bank, Punjab National Bank, Karnataka Bank, Bank of Baroda) and 5 are Private Sector Banks (ICICI Bank, HDFC Bank, Axis Bank, Kotak Mahindra Bank, IndusInd Bank). Gross NPA (%) was taken as the indicator of asset quality and Return on Assets (ROA) as the measure of profitability. Descriptive statistics were used to analyse the mean gross NPA and ROA of the selected banks. Further, GNPAs and ROA were calculated for all banks, and their ranking was done using Gross NPA and ROA to find the asset quality and performance of profitability among all banks. Since the study takes a parametric approach for testing the hypothesis, the relationship between Gross NPA and ROA was studied using Pearson's Correlation Analysis. The analysis reveals that the Gross NPAs of the Public Sector Banks are generally higher than that of Private Sector Bank and their profitability is lower. The Gross NPA and ROA show a strong and statistically significant negative correlation, which means that the banks with lower Gross NPA have higher ROA. The study findings suggests that sound credit risk management, timely loan recovery, prudent credit lending and regular review of advances are important factors that contribute to the profitability and financial stability of banks. The results offer useful implications for bank management, policy makers, and financial regulators to improve asset quality and performance of Indian banking system.